Hostages of Rome - Simon Thijs (Athens Journal of History, 2016)
These preliminary thoughts on my doctoral dissertation aim to clarify the exact meaning of the Latin word obses—in particular in contrast to the Greek ῾όμηρος. Although hostage taking might not always have secured treaties successfully, it was a common practice for centuries as it served other purposes. Roman generals presented hostages as proof of their military and diplomatic accomplishments and thus strengthened their position within the Roman nobilitas. Nevertheless, hostage taking was an important institution in Roman international relations because it went hand in hand with the concept of fides— thus personifying trustworthiness—and could obviously fulfill its "traditional" role of providing leverage, especially in dealing with "barbaric" people. The Romans did not use it to Romanize foreign princes and leaders. In taking a close look at the case of the Seleucid Demetrius, it becomes clear that this happened more or less unintentionally and was not a primary objective.